MANAGEMENT PROJECT SYSTEM - Tian, R. B.; Mlodetskyi, V. R.; Klochko, B. H. (Science and Transport Progress, 2007)
A new object of research – the «organization-project» system – has been generated. The opportunity of applying the basic provisions of functional systems and the evolutionary theory for studying the processes of such system functioning has been proved.